Effects of pre‐farrowing sow vaccination against Mycoplasma hyopneumoniae on offspring colonisation and lung lesions. (16th February 2019) - Arsenakis, Ioannis; Michiels, Annelies; Schagemann, Gabriele; Gomez‐Duran, Charles Oliver; Boyen, Filip; Haesebrouck, Freddy; Maes, Dominiek G D
Abstract : This study investigated Mycoplasma hyopneumoniae colonisation and lung lesions at slaughter in pigs from vaccinated (V) and non‐vaccinated (NV) sows, in two herds (A and B). In each herd, two sow batches were V against M. hyopneumoniae with a commercial bacterin at six and three weeks before farrowing and two sow batches remained NV. From each sow batch, laryngeal swabs were collected from the litters of five primiparous sows at weaning and seven days post‐weaning. All samples were tested for M. hyopneumoniae by nested PCR. In total, 488 piglets were sampled. At slaughter, the extent of Mycoplasma ‐like pneumonia lesions (lung lesion score (LLS)) was assessed. The colonisation rates with M. hyopneumoniae at weaning and seven days post‐weaning were (V‐A=14.2, NV‐A=20.0 (P=0.225); V‐B=0.9, NV‐B=0.8 (P=0.948)) and (V‐A=0.8, NV‐A=7.0 (P=0.039); V‐B=1.8, NV‐B=2.5 (P=0.738)), respectively. The average LLS (in per cent) was V‐A=15.5, NV‐A=26.4 (P=0.021); V‐B=9.7, NV‐B=8.4 (P=0.541). In conclusion, in herd A, with a substantially higher level of piglet colonisation at weaning than herd B, offspring from V sows had a significantly lower colonisation rate seven days post‐weaning and a significantly lower LLS at slaughter compared with the offspring of the NV sows. This implies that sow vaccination might be useful for control of M. hyopneumoniae infections, although significant results may not be achieved at all times (such as in herd B).